Discourses We Live By Narratives of Educational and Social Endeavour - Wright, Hazel R.; Høyen, Marianne (Open Book Publishers, 2020)
"What are the influences that govern how people view their worlds? What are the embedded values and practices that underpin the ways people think and act? Discourses We Live By approaches these questions through narrative research, in a process that uses words, images, activities or artefacts to ask people - either individually or collectively within social groupings - to examine, discuss, portray or otherwise make public their place in the world, their sense of belonging to (and identity within) the physical and cultural space they inhabit. This book is a rich and multifaceted collection of twenty-eight chapters that use varied lenses to examine the discourses that shape people's lives. The contributors are themselves from many backgrounds - different academic disciplines within the humanities and social sciences, diverse professional practices and a range of countries and cultures. They represent a broad spectrum of age, status and outlook, and variously apply their research methods - but share a common interest in people, their lives, thoughts and actions. Gathering such eclectic experiences as those of student-teachers in Kenya, a released prisoner in Denmark, academics in Colombia, a group of migrants learning English, and gambling addiction support-workers in Italy, alongside more mainstream educational themes, the book presents a fascinating array of insights. Discourses We Live By will be essential reading for adult educators and practitioners, those involved with educational and professional practice, narrative researchers, and many sociologists. It will appeal to all who want to know how narratives shape the way we live and the way we talk about our lives."